Poezia „pură” vs. politică: discuții la revista „Luceafărul” în anul 1975 - Ana-Maria Bănică (Revista de Istorie și Teorie Literară)
In this study we propose analyzing the discussions about post-war poetry in the way they are prefigured in special rubrics that can be found in `Luceafărul` magazine, in 1975. Literary critics, historians and poets participate in debates about poetry (What is and where turn on poetry?, Echo: What is and where turn on poetry?), or others like Voicu Bugariu start a serial of seven episodes named Poetry and political option in order to minimize the influence of pure poetry. The lyric in that period is characterized by two directions: pure poetry inquired by subjectiveness, by the recognizable style of the author, one side, and the political poetry, in which the authors defeat their ego and become spokesmen of the revolutionary people, whom they get right to progress. There do not lack the announcement of some deficits of poetry written in 1970, whose authors becomes epigones of the inter-war poets (Ov. S. Crohmălniceanu), observation that is completed by Eugen Simion who talks about the inflation of spread-eagle poetry. Al. Piru proposes an allusive game by redefining the country concept, which in the case of authentic authors meet with the poet`s inmost being, with his thinking and profound reflectiveness about life, they being the followers of eminescian visionariness, while the politic partisans rest to be the prisoner of here and now and limit themselves at the glorification of the communist ideology.